Evaluation of a New SnowPaver at McMurdo Station, Antarctica - Shoop, Sally A; Alger, Russ; Kunnari, Joel; Wieder, Wendy L (2014)
The snow roads at McMurdo Station are the primary transportation corridors to the surrounding airfields. However, during warm spells, deteriorating road conditions can seriously limit payloads for all types of vehicles. The Cold Regions Research and Engineering Laboratory (CRREL) has studied the construction and maintenance of the snow roads and teamed with the Keweenaw Research Center (KRC) and the National Science Foundation (NSF) to assess the feasibility of using a new SnowPaver to build snow roads in Antarctica. KRC built the SnowPaver, a single unit consisting of leveling blades, a milling unit, and a vibratory plate compactor, and shipped it to McMurdo in November 2010. In McMurdo, the SnowPaver constructed snow pavement sections that were monitored for performance based on snow-road strength and vehicle rutting. The SnowPaver was also used for reworking and compacting old and slushy snow during the height of the warm season. In November 2012, the power unit was upgraded; and snow roads built with the improved SnowPaver were 5 to 7 times stronger than the unprocessed road and 3 to 4.6 times stronger than the Pegasus Road. An economic analysis showed the SnowPaver would pay for itself in 1 to 5 years, depending on the usage. The original document contains color images. Prepared in collaboration with the Keweenaw Research Center, Final rept.Michigan Technological University, Houghton, MI, and the Science and Technology Corporation, Hampton, VA.